2013
DOI: 10.1007/s00431-013-2041-4
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Saccharomyces boulardii versus nystatin for the prevention of fungal colonization and invasive fungal infection in premature infants

Abstract: Prophylactic S. boulardii supplementation is as effective as nystatin in reducing fungal colonization and invasive fungal infection, more effective in reducing the incidence of clinical sepsis and number of sepsis attacks and has favorable effect on feeding intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 23 publications
2
29
0
2
Order By: Relevance
“…The probiotics, mainly lactic acid bacteria, are deemed worthy as an alternative prophylactic and therapeutic agent for managing human candidiasis ( Figure 1A and B) [127][128][129]. Although the mechanisms of action of probiotics against Candida is unclear, as yet, the major attribute of probiotics appears to be the restoration of a natural healthy microbiome in a given habitat [129].…”
Section: Probioticsmentioning
confidence: 99%
“…The probiotics, mainly lactic acid bacteria, are deemed worthy as an alternative prophylactic and therapeutic agent for managing human candidiasis ( Figure 1A and B) [127][128][129]. Although the mechanisms of action of probiotics against Candida is unclear, as yet, the major attribute of probiotics appears to be the restoration of a natural healthy microbiome in a given habitat [129].…”
Section: Probioticsmentioning
confidence: 99%
“…Candida can translocate into the bloodstream through the intact gastrointestinal mucosa and spread to visceral organs, leading to systemic candidiasis, especially in critically ill patients [3]. Disruption of normal physiological barriers, such as gastric acidity and perturbations of the indigenous microflora of the colon, facilitate Candida overgrowth.…”
Section: Extraoral and Systemic Candida Infectionsmentioning
confidence: 99%
“…The critical factors that precipitate systemic infections include the very low-birth-weight neonates [3] and immunosuppression as in HIV disease, or radiation and cytotoxic therapy [4]. Perturbation of mucosal ecosystem or marked changes in the microbial ecosystems due to antibiotics or corticosteroids, hypoendocrine states (eg, hypothyroidism, Addison disease, and diabetes mellitus), blood disorders such as acute leukemia, xerostomia due to irradiation or Sjogren syndrome, and ill-fitting appliances are predisposing factors for localized candidal infections either in healthy or diseased states [4].…”
mentioning
confidence: 99%
“…They found that both the probiotics were effective in the prevention of GIT colonization by Candida, in the protection from late-onset sepsis, and in reducing abnormal neurological outcomes. Demirel et al [4] conducted a prospective, randomized comparative study in preterm infants with a gestational age of 32 weeks and birth weight of 1500 g. The aim was to compare the efficacy of orally administered Saccharomyces boulardii versus nystatin in prevention of fungal colonization and invasive fungal infections in VLBW infants. They concluded that prophylactic S. boulardii supplementation is as effective as nystatin in reducing fungal colonization and invasive fungal infection, more effective in reducing the incidence of clinical sepsis and number of sepsis attacks and has favorable effect on feeding intolerance.…”
mentioning
confidence: 99%